New Results for Generalized Gronwall Inequalities and Their Applications - Shi-you Lin (Abstract and Applied Analysis)
In succession to our earlier work, we further provide some new generalized Gronwall inequalities and apply these inequalities to the study of qualitative estimations of solutions to certain fractional differential equations.